(untitled) (Bangladesh Journal of Agricultural Research, 2017)
Specialized Agricultural Credit (SAC) policy implemented by the Bangladesh Bank played a significant role to increase agricultural production specially spices. But documentation in this regard is scarce in Bangladesh. Therefore, this study captured the impacts of specialized credit on onion and garlic cultivation at Faridpur and Natore district respectively. The survey was conducted on two hundred farmers of which fifty were credit recipient farmers and fifty were non-recipient farmers of each district. Credit recipient farmers received on an average Tk. 26,255 for spices cultivation. Average cost to complete the process from receiving to repaying credit was Tk. 515. Farmers in the study areas utilized their maximum part of credit for spices cultivation (96.2%) followed by other crop cultivation (2.15%), family expenditure (1.4%) and business (0.25%). Due to getting credit facility farmers cultivated 16 decimals more land compared to previous years for spices, 42% of the farmers increased number of spices crop for cultivation, and farmers also increased amount of input use with better quality. For these, credit recipient farmers harvested spices with higher yield which finally helped in getting higher farm income. Credit recipient farmers received 7% higher net return from onion and 16% higher net return from garlic cultivation. Highest percentage of farmers (82%) mentioned that lack of information about spices credit was the main reason behind not receiving credit facility by large number of farmers. Specialized credit facility for farmers need to be widened through spreading information of spices credit facility among the farmers and increasing amount of credit.Therefore, domestic production of spices will increase and imports of spices from abroad will decrease. Bangladesh J. Agril. Res. 42(2): 233-247, June 2017